Analisis Faktor yang Mempengaruhi Minat Petani dalam Penggunaan Paenibacillus polymyxa untuk Pengendalian Jamur Blas pada Tanaman Padi Di Kalurahan Girijati Kapanewon Purwosari Kabupaten Gunung Kidul - Habib Mustofa Syaifudin; Sukadi Sukadi; Ananti Yekti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the factors that influence farmers' interest in using Paenibacillus polymyxa as a control agent for blast fungus (Pyriculariaoryzae) on rice plants in Girijati Village, Purwosari District, Gunung Kidul Regency. The research approach used was quantitative with a surveymethod of 36 rice farmers selected through random sampling techniques. Data were collected using a questionnaire that had been tested for validity and reliability, then analyzed using multiple linear regression with the help of SPSS software. The results showed that simultaneously, allindependent variables studied had a significant influence on farmers' interest. However, partially, only the role of women's farmer groups showed asignificant influence. These findings indicate that a group-based approach, especially involving women's farmer groups as local facilitators, is ableto build trust and increase the adoption of biotechnology by farmers. Meanwhile, the role of extension workers and individual factors such as age,formal education, non-formal education, business experience, land area, income, farmers' interest in participating in extension, and frequency ofattending extension have not provided a significant direct influence. Therefore, the strategy for developing the adoption of environmentally friendly agricultural technology needs to focus on strengthening farmer institutions and collaborative support at the local level